PSIKOTERAPI PENDEKATAN SUFISTIK DALAM MENANGANI MASALAH AGAMA DAN MORAL REMAJA - Dasril Dasril (Ta'dib, 2008)
This article discusses conceptually the approach of suffistic psychotherapy in handling religious and moral problems of Moslem teenagers. Among those problems are: drug abuse, drunks, students fights, free sex, and lack of religious practices. The above mentioned approach is believed to be able to solve the problems by encouraging the teenagers to recite the Holy Qoran, to perform late night prayer (qiyamul lail), to do fasting (compulsory and optional as well), to pray and to have self evaluation (muhasabah) more.Kata kunci : psikoterapi sufistik, menangani masalah agama, dan moral remaja